UMP Kilau volunteers serve the community in KL - MUHAMMAD ZUFLI, ZUHAIRI (2023)
KUALA LUMPUR, 2 April 2023 - A total of 50 UMP Kilau volunteers in Yayasan UMP Squad and Universiti Malaysia Pahang (UMP) alumni joined Projek Secangkir Budi as one of the initiatives to help underprivileged people around Kuala Lumpur.